Subjective vision assessment in companion dogs using dogVLQ demonstrates age-associated visual dysfunction - Rogers, Callie M.; Salzman, Michele M.; Li, Zhanhai; Merten, Natascha; Russell, Leah J.; Lillesand, Hannah K.; Mowat, Freya M. (Frontiers in Veterinary Science, 2023)
Dim light vision as assessed by proxy and clinical tools is commonly impaired in older humans and impacts quality of life. Although proxy visual assessment tools have been developed for dogs, it is unclear if they are sensitive enough to detect subtle visual dysfunction in older dogs. We sought to determine if a newly designed proxy visual function questionnaire could detect age-associated differences in visual behaviors in varying lighting conditions in dogs. A 27-item questionnaire (the dog variable lighting questionnaire, dogVLQ) was designed to assess visual behavior in dogs in different lighting settings. We conducted the dogVLQ, a previously validated visual function questionnaire (the dog vision impairment score), and performed light- and dark-adapted electroretinography (ERG) on a subset of dogs. Questionnaire scores were analyzed for dog age associations using correlation analysis. Questionnaire responses from 235 dog owners were obtained (122 female, 112 male dogs), 79 of which underwent ERG (43 female, 36 male dogs). Bright light visual behavior was significantly associated with light-adapted bright flash ERG amplitudes, visual behavior in near darkness was associated with dark-adapted ERG amplitudes. The dogVLQ identified worse vision in older dogs in bright light, dim light, and darkness; predicted onset was younger for vision in near darkness. Older dogs had more difficulty navigating transitions between lighting conditions. Subjective dog owner assessment of visual function associates with objective measurement of retinal function in dogs and supports reduced vision-mediated behaviors in older dogs.